Aspecto verbal en la evolución de la construcción catalana "anar + infinititu" - Nagy, Katalin C. (Acta Hispanica, 2008)
The paper presents the special characteristics of the Catalan past perfect tense. In the majority of languages, and, more specifically, in neo-latin languages, similar structures, containing verbs of movement tend to modify into future tense. As opposed to this, the structure“anar + infinitive” stands for past perfect in modern Catalan. The perfect aspect component raises the question of how this tense became grammaticized, a process examined by the author from the historic pragmatic point of view. There are two main hypotheses concerning the aspect of the medieval antecedent of the structure. According to the so-called inchoative hypothesis, the medieval “anar + infinitive” was an inchoative periphrasis. The other thesis attributes past perfect quality to the structure already in medieval Catalan. The perfect aspect can be traced back either to the verbal aspect of the auxiliar verb in past perfect, rather common in medieval Catalan structures, or, in earlier sources, to the lexical aspect of perfect-aspect verbs in the structure. The author employs two main lines of methodology: on the one hand, the phenomenon is analyzed in correlation with structures similar either in form or function; on the other hand, it considers the more ample context of medieval use. The author concludes that the modern Catalan past perfect is not rooted in an inchoative periphrasis, but evolved from a compound structure expressing intention, which probably gave rise to pragmatical conclusions in its contexts of use. As a result of these pragmatical conclusions, the meaning of the structure transformed from a structure with a perfect or completive aspect into the past perfect tense of modern Catalan.